MODELING OF SYRINGE CLAMPING AND ROLLING FOR SYRINGE GRINDING PROCESS - Abraham Bangun, Billy
As time goes by, syringes demand continues to increase. To fulfil the increasing demand for syringes, specific tools are needed to mass-produce syringes according to geometry specifications. One of the tools that can be used to overcome these problems are jig and fixture. Jig and fixture are mounted on a grinding machine so that it can speed up and simplify the grinding process. Jig and fixture has been made in Adi Sutowijoyo’s Final Year Project (13114096). However, during grinding process, errors were found so that needles obtained were not optimal. This research begins by identifying errors in the jig and fixture and then modeling the process that occurs in the chuck with the Ansys software. Modeling is used to obtain materials effect on clamping and rolling process. Materials used for the simulation are polyurethane, aluminium alloy, polyethylene, dan steel (ST 37). After modeling, the results obtained are processed using theoretical equation. Afterward, results from rolling process are used to solve existing problema. Based on the simulation results, physical properties of material (modulus of elasticity, Poisson's ratio, and coefficient of friction) contribute on rolling process so there are differences in slip value. The smallest slip value in order as follows : polyurethane, aluminium alloy, polyethylene, dan steel (ST 37). With the slip value obtained, material for rolling process that can be in accordance with the geometry specifications is polyurethane.